Charge separation and isolation in strong water droplet impacts. Issue 10 (12th February 2015) - Wiederschein, F.; Vöhringer-Martinez, E.; Beinsen, A.; Postberg, F.; Schmidt, J.; Srama, R.; Stolz, F.; Grubmüller, H.; Abel, B.
Abstract : A schematic picture of the phenomenon of charge separation and charged droplet formation after high-energy impact in condensed matter. Abstract : Charge separation in condensed matter after strong impacts is a general and intriguing phenomenon in nature, which is often identified and described but not necessarily well understood in terms of a quantitative mechanistic picture. Here we show that charge separation naturally occurs if water droplets/clusters or ice particles with embedded charge carriers, e.g., ions, encounter a high energy impact with subsequent dispersion – even if the involved kinetic energy is significantly below the molecular ionization energy. We find that for low charge carrier concentrations ( c < 0.01 mol L −1 ) a simple statistical Poisson model describes the charge distribution in the resulting molecular "fragments" or aggregates. At higher concentrations Coulomb interactions between the charge carriers become relevant, which we describe by a Monte Carlo approach. Our models are compared to experimental data for strong (laser) impacts on liquid micro beams and discussed for the charge generation in cluster-impact mass spectrometry on cosmic dust detectors where particle kinetic energies are below the plasma threshold. Taken together, a simple and intuitive but quantitative microscopic model is obtained, which may contribute to the understanding of a larger range of phenomena related to charge generation and separation in nature.